Overexpression of eelgrass Rare Cold Inducible 2 (RCI2) maintains chlorophyll content in Arabidopsis subjected to high salinity and dehydration - Masahiro Senuma; Shohei Dobashi; Yukiko Bando; Sukmin Ko; Hajime Shiota (Plant Stress, 2022)
Eelgrass (Zostera marina) is a monocotyledonous plant found in seawater (seagrass). Eelgrass has many physiological characteristics that enable it to cope with salinity, hyperosmolarity, and hypoxia, as well as to live in marine environments. Germinating seedlings are sensitive to high levels of salinity, which inhibit germination and seedling growth. Thus, potent mechanisms likely protect eelgrass seedlings during early development. In this study, to identify the eelgrass genes required for abiotic-stress tolerance, 57 genes that are highly expressed during seed germination were isolated from a cDNA library derived through seed germination. We focused on ZoRCI2B, which encodes the small-membrane protein RCI2 thought to be involved in various stress tolerance responses. ZoRCI2B expression was high during seed germination and low in mature plants. Expression was upregulated under high water temperature and high salinity, and by dehydration and low dissolved-oxygen concentrations in leaves. The results of this study imply that ZoRCI2B may participate in adaptation to various abiotic stresses. Growth inhibition was reduced and chlorophyll content was maintained at higher levels in ZoRCI2B-overexpressing Arabidopsis exposed to salinity or dehydration. However, various temperature and flooding culture conditions led to no differences in the growth of overexpressing or wild-type plants. These results indicate that ZoRCI2B maintains chlorophyll content under salinity and dehydration stress, and could be applied to impart stress tolerance to various plants.